Recession in the economy of the Republic of Moldova - Boris Gaina; Svetlana Fedorchukova; Galina Kobirman (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
The economy of the Republic of Moldova has entered, since 2009, an economic recession, which has become deep in the last period of 2019-2021. Previously, the Republic of Moldova was severely affected by the so-called "theft of the billion" from the three state-owned banks, which caused great damage to the state economy, and also was affected by the drought of 2019-2020. The situation became instantly critical, when the whole world was affected by the virotic pandemic, caused by STAR Cov-2, the consequences of which became detrimental to the economy and social life of this state. A large number of employees lost their jobs, and part of the active population was placed in isolation and quarantine. Production and trade relations have been severely distorted and activities in the HORECA system have been suspended for a long time. The research / development system also suffered a lot, due to insufficient funding and the decrease in the volume of technology transfer works obtained under state programs, as well as cross-border projects and those funded by the European Union.
Keywords: O3; Q1; 330; economic recession; gross domestic product; research / development; drought; pandemic